A COMPARATIVE CLINICAL STUDY OF MESHASHRINGI (GYMNEMA SYLVESTRE) AND MAMAJJAKA (ENICOSTEMMA LITTORALE) IN THE MANAGEMENT OF MADHUMEHA (TYPE ll DIABETES MELLITUS) (International Journal of Food and Nutritional Sciences, 2021)
Diabetes Mellitus, particularly Type 2 (Madhumeha), is a chronic metabolic disorder marked by elevated blood glucose levels and associated complications. This study aimed to evaluate the efficacy and safety of two Ayurvedic herbs, Meshashringi (Gymnema sylvestre) and Mamajjaka (Enicostemma littorale), in managing Madhumeha.